AN ANALYSIS OF THE TRANSLATION OF PHRASAL VERBS IN A NOVEL WRITTEN BY NELSON DEMILLE ENTITLED THE GENERAL DAUGHTER - M Wahyu Dermawan, - (2009)
This paper is entitled An Analysis of The Translation of Phrasal Verbs in a Novel Written by Nelson Demille Entitled The General's Daughter. The study was aimed to find out the types of phrasal verbs mostly found in the novel and find out the translation strategies applied by the translator in translating phrasal verbs in the novel. This study is based on descriptive qualitative method to present the data gained from the document. Random sampling method was applied to pick a hundred samples from all phrasal verbs found in the novel. The data were categorized based on Brown's constructions of phrasal verbs (2002) namely transitive separable, transitive inseparable and intransitive inseparable phrasal verbs. The findings of the study showed that transitive separable phrasal verb was the most frequent type of phrasal verbs found in the novel. The strategies used are those which are proposed by Baker (1992); translation by using an idiom of similar meaning and form, using an idiom of similar meaning but dissimilar form, by paraphrasing and by omission. The finding showed that paraphrase strategy was the most dominant strategy used by the translator in translating the phrasal verbs. Omission strategy came second and using an idiom of similar meaning and dissimilar form was the third frequent strategy applied. Translation by using an idiom of similar meaning and form was not applied by the translator in translating the phrasal verbs found in the novel.